Inna wiara, inny Bóg. Problem wiary w twórczości lirycznej Tadeusza Różewicza - Krupa, Renata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
At the beginning of my article I present the themes, symbols and quotations which refer to the Bible and I discuss their functions. Afterwards, I show the image of God embodied in Różewicz’s poetry. First, this God is helpless and submissive to history and poeple. Then, he is the almighty Creator who supports a man. Subsequently, I present Różewicz as a poet who converted from atheism to faith. Early on, the author was demonstrating his departure from God caused by his war experiences. He felt that God had died and in this connection all the values precious for a man had died too. In spite of this, the faith remained in the local point of Różewicz’s autlook on life. The author often looked back on his childhood when he had been close to the Lord. He became aware of lack of spiritual prime in his liľe. He also knew that life without God turns into merely a phisical existence. Finally, he found the real faith and wrote pieces which we can consider as his declaration.